2021
DOI: 10.1016/j.asmr.2021.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Women and Men National Collegiate Athletic Association Ice Hockey Players Were Similarly Likely to Suffer Lumbar Spine Injuries

Abstract: Purpose To describe and compare the epidemiology of lumbar spine injuries (LSIs) in women’s and men’s ice hockey during the 2009-2010 to 2013-2014 academic years and to investigate sex-specific differences, using data from the National Collegiate Athletic Association (NCAA) Injury Surveillance Program (ISP) database. Methods The incidence and characteristics of LSIs were identified utilizing the NCAA ISP. Rates of injury were calculated as number of injuries divided by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…There are a small number of existing studies that contrast injuries sustained during ice hockey by the sex of the player. Studies based on National Collegiate Athletic Association (NCAA) ice hockey data demonstrated that rates of lumbar spine fractures 19 and back/neck/spine injuries in general 20 were comparable between the sexes. Interestingly, one recent study on the incidence of upper extremity injuries sustained during hockey demonstrated that men sustained a higher rate of injury than did women, 21 a finding which conflicts with the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a small number of existing studies that contrast injuries sustained during ice hockey by the sex of the player. Studies based on National Collegiate Athletic Association (NCAA) ice hockey data demonstrated that rates of lumbar spine fractures 19 and back/neck/spine injuries in general 20 were comparable between the sexes. Interestingly, one recent study on the incidence of upper extremity injuries sustained during hockey demonstrated that men sustained a higher rate of injury than did women, 21 a finding which conflicts with the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Over the study period, there were 306 patients with hockey-related injuries (<1% of all patients in the NTDB). The median age was 15 [13][14][15][16][17][18][19][20][21][22][23][24][25] years and ranged from 5 to 71 years (Table 1). The majority of patients were male (n = 279, 91%).…”
Section: Patient Demographics Clinical Data and Injury Datamentioning
confidence: 99%